If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -34 = 2(5k + 8) + 5(k + 2) Reorder the terms: -34 = 2(8 + 5k) + 5(k + 2) -34 = (8 * 2 + 5k * 2) + 5(k + 2) -34 = (16 + 10k) + 5(k + 2) Reorder the terms: -34 = 16 + 10k + 5(2 + k) -34 = 16 + 10k + (2 * 5 + k * 5) -34 = 16 + 10k + (10 + 5k) Reorder the terms: -34 = 16 + 10 + 10k + 5k Combine like terms: 16 + 10 = 26 -34 = 26 + 10k + 5k Combine like terms: 10k + 5k = 15k -34 = 26 + 15k Solving -34 = 26 + 15k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-15k' to each side of the equation. -34 + -15k = 26 + 15k + -15k Combine like terms: 15k + -15k = 0 -34 + -15k = 26 + 0 -34 + -15k = 26 Add '34' to each side of the equation. -34 + 34 + -15k = 26 + 34 Combine like terms: -34 + 34 = 0 0 + -15k = 26 + 34 -15k = 26 + 34 Combine like terms: 26 + 34 = 60 -15k = 60 Divide each side by '-15'. k = -4 Simplifying k = -4
| -2992+272m=0 | | -7x+5+5x=3 | | 5cos^2x-2sinx=2 | | 3-6=2x-3 | | n/2=-1/34 | | 4+4x+3x=-10 | | Y^2=16/64 | | -.8x=24 | | Q^2=225 | | |1/3d-6=15| | | -5x+1=-6x-6 | | 5(x+1)=63-2x-2x | | 50=6(n+8)-(8n-6) | | 1-x+7x=55 | | -7x+4+2x=39 | | -33=-3(r+5)-3(-6r+6) | | 3x^4+7x^3+18x=0 | | 1-7x+3x=-27 | | 3b-5z=8 | | 19=3(g+3)+1 | | -1/12x=1/4 | | -38+6x=4(8x-3) | | 4(x-1)-2(3x-2)=3-5(x-3) | | 2(p+2)=16 | | 7/2=21/6 | | 18+5b=3b | | 2(c+14)=37 | | -(8+7p)=-6p-13 | | 11=-5x-5x-9 | | =13-v | | g/2-4g=20 | | (-2/5)x=-4/15 |